The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1046/j.1460-9568.2000.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in the nigrostriatal pathway in response to increased 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine‐induced neurodegeneration in the mouse

Abstract: Although several adaptive mechanisms have been identified that mask the existence of Parkinson's disease and delay the onset and aggravation of motor symptoms, the timescale and implications of this compensatory process remain an enigma. In order to examine: (i) the nature of the dopaminergic adaptive mechanisms that come into action; (ii) their sequential activation in relation to the severity of degeneration; and (iii) their efficacy with regard to the maintenance of a normal level of basal ganglia activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 51 publications
5
45
3
Order By: Relevance
“…The latter phenomenon has been reported in spontaneously recovering MPTP cats (Schneider et al, 1994) and rats with partial 6-OHDA lesions (Dentressangle et al, 2001). This diffusion could be facilitated by the volume transmission (Fuxe and Agnati, 1991) promoted under DA depletion (Robinson and Whishaw, 1988) and by a decrease in the number of DA reuptake sites in the striatum (Bezard et al, 2000(Bezard et al, , 2001. We found that associative-limbic DA levels after recovery were similar to those in the normal state.…”
Section: Relevance Of Repeated Microdialysis For Investigating Neurocmentioning
confidence: 53%
“…The latter phenomenon has been reported in spontaneously recovering MPTP cats (Schneider et al, 1994) and rats with partial 6-OHDA lesions (Dentressangle et al, 2001). This diffusion could be facilitated by the volume transmission (Fuxe and Agnati, 1991) promoted under DA depletion (Robinson and Whishaw, 1988) and by a decrease in the number of DA reuptake sites in the striatum (Bezard et al, 2000(Bezard et al, , 2001. We found that associative-limbic DA levels after recovery were similar to those in the normal state.…”
Section: Relevance Of Repeated Microdialysis For Investigating Neurocmentioning
confidence: 53%
“…Interestingly, in addition to a potential role in METH-induced DA neurotoxicity, alterations in COX activity have been reported after lesions induced by several classic neurotoxins, including MPTP, 6-OHDA, and quinolinic acid. For example, COX activity increases in the substantia nigra pars reticulata 20 d after MPTP lesions, with no changes at earlier times (Bezard et al, 2000). Conversely, using similar methods, rats receiving lesions in the striatum with the excitotoxin, quinolinic acid, were noted to have highly significant reductions in COX activity in several basal ganglia structures (including striatum but not substantia nigra pars compacta or pars reticulata) 1 week after injury, whereas rats lesioned with intrastriatal 6-OHDA did not show any changes in COX activity in any of the above regions (Levivier and Donaldson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These include increased levels (per cell) of tyrosine hydroxylase (TH) mRNA in the substantia nigra and ventral tegmental area (Joyce et al 1997;Tong et al 2000), and TH protein in the striatum (Bezard et al 2000), possibly by increased transcriptional activation of the TH gene. Similar changes in noradrenergic neurons were reported by Burke et al (1999) in a series of AD cases in which substantial (79%) cell loss within the LC was observed together with an 11-fold increase in DβH protein in the remaining neuronal cell bodies.…”
Section: Plasma Dβh and Dbh Genotypes In Neurodegenerative Diseasesmentioning
confidence: 99%